IMPLEMENTASI BIMBINGAN KELOMPOK DALAM MENINGKATKAN KEDISIPLINAN SANTRI DI PONDOK PESANTREN MODERN DAN TAHFIZH DARUL UMMAH - Muthiah Farhah Nabila; Nur Azmi Wiantina; Putri Rahayu S (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
This study aims to explore the contribution of group guidance services to improving the personal discipline of santri, namely behavioral changes that arise from individual awareness and responsibility, rather than merely from rules or sanctions. Using a qualitative approach with a case study design, this research involved four santri selected through purposive sampling. Data were collected through in-depth interviews, participant observation, and related document analysis, then analyzed using thematic analysis techniques. The results show that group guidance services facilitate improved discipline through three main mechanisms: increasing self-awareness of regulations, developing time management skills, and providing social support from fellow group members. Active participation in discussions and group dynamics encouraged santri to reflect on their behavior, foster motivation for change, and internalize discipline values sustainably. These findings confirm that group guidance is effective as a holistic disciplinary development medium, going beyond external compliance. This study provides practical implications for guidance and counseling teachers and pesantren administrators to routinely integrate group guidance into student development, in order to foster internal motivation, responsibility, and orderly behavior among santri.